The Development of Resistivity Equipment for Subsoil Investigation - Jaisumroum, Nattapon (International Journal of Engineering and Technology, 2018)
This research aimed to develop the resistivity equipment for a groundwater investigation using 2D electrical resistivity technique. 2D electrical resistivity measurement was carried out at one profile with 90 meters long at Soi Dao district in Chantaburi Province, Thailand, where most of the areas are quite mountainous and longan plantation. Wenner electrode array was selected for 2D electrical resistivity measurement. The results showed that the instrument could be used to measure subsoil resistivity by using less capital cost with more convenient by weight and size and higher efficiency in depth measurement due to the higher voltage.Â Â